Impact of the COVID-19 Pandemic on Functional Urology Practice: A Nationwide Survey From Turkey - Ahmet TAHRA; Murat DINCER; Rahmi ONUR (Medeniyet Medical Journal)
Objective: Routine urology practice has changed with the coronavirus disease-2019 pandemic. We aim to determine the urologists' functional urology practice during the pandemic by an online questionnaire. Methods: An online questionnaire was conducted to assess the functional urology practice of Turkish urologists' during the pandemic. The workplace, positioning as a pandemic hospital, involvement in pandemic clinics, and the relevance to functional urology were questioned. We also inquired about outpatient services, diagnostic tests, and elective surgeries during the pandemic compared with their routine practice. Results: One hundred and fifty-two participants completed the questionnaire. Of these, 32.2% replied that more than half of their daily practice was related to diagnosing and treating incontinence, prolapse, and neurourology. According to 123 participants (80.9%), there was a decrease in outpatient clinics. Diagnostic tests were also reduced, such as uroflowmetry (68.4%) and urodynamics (81.3%). The majority of respondents declared a decrease in elective surgeries as Botox injection (92.1%), surgery for urinary incontinence (93.4%), and surgery for prolapse (85%). Nearly one-quarter of respondents' (28.9%) stated that their diagnostic methods for neurourology patients did not differ. Conclusions: One of the most affected areas in urology during a pandemic is functional urology. Although diagnostic tests and surgery for functional urology are classified as 'optional,' the quality of life of patients will be affected by the delayed intervention.